Schelling & Plato - Harry, Chelsea (Palgrave handbooks in German idealism, 2026)
Keywords: Dialectic; Mythology; Natural (archaeology); Opposition (politics); Reflexive pronoun; dept.phi

Has εὐβίοτος in Aristotle’s Historia Animalium ix Been Mistranslated? - Harry, Chelsea (Journal of Ancient Philosophy, 2025)
Le terme εὐβίοτος, « bien vivre », et ses équivalents apparaissent dans les observations d'Aristote sur les oiseaux, dans l'Historia Animalium IX. Cette note de recherche compare la façon dont le terme aristotélicien a été traduit dans les manuscrits grecs, latins et arabes, ainsi que dans les traductions modernes et contemporaines en anglais, français et allemand, et démontre qu'il a été mal traduit, à commencer par les traducteurs humanistes du XVe siècle, Georges de Trébizonde et Théodore Gaza. Les libertés prises dans la surinterprétation du terme aristotélicien ont peut-être obscurci ce qu'il cherchait à communiquer sur les capacités des oiseaux.
Keywords: Art; Epistemology; Literature; Philosophy; dept.phi

John Dewey - Haitos, Alexander (J.B. Metzler eBooks, 2025)
Keywords: Epistemology; Philosophy; Sociology; dept.phi

John Locke - Haitos, Alexander (J.B. Metzler eBooks, 2025)
Keywords: Philosophy; Political science; Sociology; dept.phi

Zeitloser Gegenstand - Haitos, Alexander (J.B. Metzler eBooks, 2025)
Keywords: Philosophy; Political science; dept.phi

Human Intelligence and Artificial Intelligence in Collaboration: Change Management, Creative Performance, and Societal Expectations - Goralski, Margaret; Górniak-Kocikowska, Krystyna (Future of business and finance, 2026)
Keywords: Applications of artificial intelligence; Artificial intelligence; Artificial psychology; Change management; Collaboration; Creative performance; Creativity; Human intelligence; Societal expectations; dept.phi

Living well in extended reality: Training phronesis and Socratic humility in XR - Gabriels, Katleen; Volkman, Richard (Journal of Moral Education, 2025)
Practical wisdom is the intellectual virtue relating to the ability to fix ends and discern in a concrete circumstance how to achieve those ends. It is cultivated through engagement with experience rather than book learning. However, a whole matrix of convergent technologies, such as headsets, haptic suits, AI-driven chatbots, and extended realities, such as augmented and virtual reality (AR/VR), creates new conditions for training practical wisdom. How can moral educators facilitate practical wisdom in this extended reality (XR)? Drawing on Nussbaum’s account of phronesis, we contend the job of moral education in XR is mostly about ensuring students’ critical engagement. We suggest AI assistants can contribute to this task, so long as these technologies and the people using them manifest Socratic humility ensuring that no single interaction serves as an ‘oracle of truth’, leaving critical thinking and judgment firmly in the hands of the student.
Keywords: Environmental ethics; Epistemology; Extended reality; Humility; Hypocrisy; Pedagogy; Philosophy; Phronesis; Psychology; Social psychology; Sociology; Socratic humility; Socratic method; Theology; Training (meteorology); convergence; dept.phi; phronesis

Denialism and its consequences: the epistemic injustice of national narratives - Marsoobian, A.T. (Pragmatism Today, 2024)
An analysis of how national narratives are inevitably forms of epistemic injustice, depriving individuals of epistemic and moral agency. Denying access to knowledge about the past is a tool of all autocratic regimes, commonly used for the purpose of retaining power and exerting dominance over individuals or groups subordinate to the ruling elite. Yet such narratives and the falsifications used to buttress them, are not the exclusive instruments of autocracies but can be found to pervade the national narratives of what we often nominally label as democracies. The denial of crimes against humanity and genocide are the most egregious examples of the harms perpetrated against victims and survivors. Miranda Fricker’s writings on epistemic injustice are employed in the analysis. Turkish and Azerbaijani genocide denial of the Armenian Genocide are used to illustrate how epistemic injustice lies at the heart of denialism. © 2024 Central European Pragmatist Forum. All rights reserved.
Keywords: Melanie Altanian; Miranda Fricker; denialism; dept.phi; epistemic injustice; genocide; national narratives; peer-reviewed

Team building-it is all about people, the mission, and values - Goralski, M.A.; Górniak-Kocikowska, K. (Technology Entrepreneurship in Theory and Practice: Perspectives in Science and Engineering, 2025)
Keywords: dept.phi

Plato on Women’s Natural Ability: Revisiting Republic V and Timaeus 41e3–44d2 and 86b1–92c3 - Harry, Chelsea; Ron, Polansky (Apeiron, 2016)
Abstract Despite the prominent argument for equal educational opportunity for women in Republic V, commentators frequently question Plato’s sincerity, the quality of the case made, or its significance. Undermining confidence in Plato’s advocacy of female equality are derogatory remarks about women in this and other dialogues. Since we take Plato to be sincere in the argument in Republic V, we reconcile his conclusions there about the equal educational opportunity for women with these seemingly problematic remarks by suggesting that the remarks reflect the interlocutors involved in the dialogue and conventional Athenian prejudices of that time rather than ideas that Plato held to be true. We take seriously the observation of Levin 1996, 14, “in none of those passages in which Plato makes derogatory remarks about women does he use phusis to explain why they behave in the ways of which he is critical.” Hence Plato never suggested that women were by nature limited to the position they occupied socially and politically in 5th or 4th century Athens; he understood the difference between the way they were by convention and the way that they could be, in accordance with their nature, were they to develop their natural capacities through education. We examine carefully Plato’s argument for the equal nature of women in Republic V to defend its viability. The provocation is our not finding in the extensive secondary literature a really detailed treatment of the actual argument and appreciation that it is intended as a sound philosophical argument. We then turn to the devolution schemes in Timaeus 41e–44d and 86b–92c, which again touch on the nature of women and appear to counter the position we attribute to Plato, to show that they are really supportive of our account. Both the Republic and Timaeus limit the natural differences between males and females to body-type. Therefore, even relative physical weakness of women’s bodies does not much problematize for Plato that their natural abilities are equal to those of men, where nature in these contexts means suitability to perform certain functions.
Keywords: dept.phi

Reframing the issue in 13.18 of the analects of Confucius: family privileges in criminal litigation and the Confucian insight - Yang, Xiaomei (Dao, 2024)
The sheep case in Analects 13.18 has generated a heated debate in contemporary Chinese philosophy for more than a decade. One side in this debate criticizes Confucius’ view in the sheep case and the other side defends Confucius’ position. Neither side’s reading of 13.18 is satisfactory. I argue that something important in the text has been overlooked and this omission may explain why neither side gives a satisfying reading. I offer in this essay a new reading of the sheep case which pays attention to what the existent interpretations have overlooked in the text. This new focus will give us a new perspective to reframe the issue in question and to defend the Confucian position in a more convincing way. On the new interpretation, Confucius’ position in the sheep case suggests a sensible and reasonable way for the state to balance some important social interests which the state seeks to protect.
Keywords: Criminal prosecution; Family privilege; Filial piety; Sheep case; dept.phi; peer-reviewed

Aesthetics - Marsoobian, A.T. (The Bloomsbury Handbook of Pragmatism, 2024)
Keywords: dept.phi

The power of personal archives in witnessing, teaching, and visual storytelling: the Armenian memory project - Masud, Catherine; Marsoobian, Armen T (Journal of Human Rights Practice, 2024)
Abstract The Armenian Memory Project (AMP) is a collaborative effort designed to harness the energy and resources of the University of Connecticut and the New England Armenian community for the goal of fostering greater understanding of the region’s Armenian cultural heritage and the impact human rights crimes had on the Armenian community. In 2019, students and faculty from the university worked with Armenian American institutions and individuals on an initial component of the AMP, employing digital media technology to tell the story of one immigrant Armenian family, the Dildilians. A unique course was created to produce a documentary film centring around this family’s experiences in Ottoman Turkey before, during, and after the Armenian Genocide. Designed and taught by a documentary filmmaker with support from a family archivist/historian, the course brought students together in a collaborative learning experience. By immersing themselves in the family’s extensive photograph archive, these students came to understand the important role that the past continues to play in the lives of present-day Armenians. Furthermore, by taking on the responsibility as storytellers of the Dildilian narrative, students developed a deeper identification with this distant history and, in a wider sense, an appreciation for the ethical value of memory in bearing witness to the past. This collaborative and participatory framework for teaching using archival collections can serve as a model for creating a transformative learning experience in the study of human rights, war, and genocide.
Keywords: dept.phi; peer-reviewed

Introduction - Harry, C.C.; Vlahakis, G.N. (Women in the History of Philosophy and Sciences, 2023)
Since the last quarter of the twentieth century there has been growing interest in women’s contributions to the histories of science, philosophy, and literature dating back to the very beginnings of these disciplines. This volume offers a contemporary, multinational, multidisciplinary exploration of some of these "hidden figures". © 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: dept.phi

On the Perception of Time in Ancient Greece - Harry, Chelsea C (In Anderen Zeiten/In Other Times: Zeitdiskurse im Wandel/ Changing Discourses of Time across Human History, 2022)
Keywords: dept.phi

Schelling and Plato - Harry, Chelsea C (Palgrave Schelling Handbook, 2023)
Keywords: dept.phi

New Sappho as a Philosopher of Time? - Harry, Chelsea C (Women in the History of Philosophy and Sciences, 2023)
Keywords: dept.phi

Sappho of Lesbos and the Time of Erosophy - Harry, Chelsea C (Routledge Handbook on Women and Ancient Greek Philosophy, 2024)
Keywords: dept.phi

Introduction: Schelling and the Environment - Harry, Chelsea C. (Environment, Space, Place, 2022)
Keywords: dept.phi

Brill's Companion to the Reception of Presocratic Natural Philosophy in Later Classical Thought - Harry, Chelsea C; Habash, Justin (Brill, 2021)
Keywords: Ancient Philosophy; Classical Studies; Classical Tradition & Reception Studies; History; History of Science; Philosophy; Philosophy of Science; dept.phi

Exploring the Contributions of Women in the History of Philosophy, Science, and Literature, Throughout Time - Harry, Chelsea C.; Vlahakis, George N. (Springer, 2023)
This book explores contributions by some of the most influential women in the history of philosophy, science, and literature
Keywords: dept.phi

Genocide by other means: heritage destruction, national narratives, and the Azeri assault on the indigenous Armenians of Karabakh - Marsoobian, Armen T. (Genocide Studies International, 2023)
The propaganda efforts of the authoritarian Aliyev regime in Baku and the general Western ignorance of the history of the South Caucasus have contributed to the lack of meaningful response to the genocidal aggression that Azerbaijan has inflicted on the indigenous Armenians of Artsakh, known to many as Nagorno-Karabakh. The humanitarian crisis created by the Azeri blockade of the Lachin Corridor is only the most recent step in a process of cleansing the region of its Armenian population, a process that began in the early years of the twentieth century. The Ottoman Turkish genocide of Armenians in 1915–1923 is not a distinct event of the past but a process whose ideology is central to the Azeri-Turkish genocidal violence perpetrated against Armenians in the present. An integral component of the processes of genocide is cultural heritage destruction as noted by Raphael Lemkin. The erasure of most signs of the indigenous Armenian presence on its historic homeland was particularly pronounced in the decades following the Armenian Genocide and continues today. Cultural erasure went hand in hand with Turkish state genocide denial and the rewriting and mythologizing of its national narrative. Azerbaijan has been following a similar playbook since the collapse of the Soviet Union. These genocidal processes of denial, heritage destruction, and the rewriting of history are what I describe as “genocide by other means.”
Keywords: dept.phi; genocide; heritage destruction; national narratives; peer-reviewed; violence

Novelty and Creativity. - Gilliland, Rex (2009)
Keywords: dept.phi; faculty_collection

Education in the Global Knowledge Society. - Gorniak, Krystyna (2007)
Keywords: dept.phi; faculty_collection; sabbatical_report

Creating Two Book Manuscripts. - Bynum, Terrell (2001)
Keywords: dept.phi; faculty_collection; sabbatical_report

Psychoanalysis and Repetition: Why Do We Keep Making the Same Mistakes? - Nasio, Juan-David (SUNY series in contemporary French thought, 2019)
In Psychoanalysis and Repetition, Juan-David Nasio, one of the leading contemporary Lacanian psychoanalysts in France, argues that unconcious repetition represents the core of psychoanalysis as well as no less than the fundamental constitution of the human being--back cover.
Keywords: Lacan, Jacques, 1901-1981; Psychoanalysis; Repetition (Philosophy); dept.phi; faculty_collection

Chronos in Aristotle's Physics: On the Nature of Time - Harry, Chelsea C. (SpringerBriefs in philosophy, 2015)
Keywords: Aristotle. Physics; Time; Philosophy; Philosophy of nature; Philosophy; Physics; dept.phi; faculty_collection

Sabbatical leave report: sabbatical Fall 2013 - Volkman, Richard (2013)
This sabbatical leave was devoted to revising and editing material for a book project with the working title, Meditations on Heroic Individualism. The principle objective was to have a finished manuscript, ready for submission to publishers. Additionally, a proposal was developed to add Special Topics course, Ethical Individualism, as a permanent course.
Keywords: dept.phi; faculty_collection; sabbatical_report

The "Backwards, Forwards and Sideways" Changes of Ict: Ethicomp 2010: Proceedings of the Eleventh International Conference - International Conference on the Social and Ethical Impacts of Information and Communication Technologies (11th : Universitat Rovira i Virgili, Tarragona; Arias-Olive, Mario; Bynum, Terrell Ward; Rogerson, Simon; Torres-Coronas, Teresa; Centre for Computing and Social Responsibility (Universitat Rovira i Virgili, 2010)
"The purpose of this series is to provide an inclusive European forum for discussing the ethical and social issues associated with the development and application of Information and Communication Technology (ICT). The conferences are held every 18 months."--Introduction.
Keywords: Congresses; Congresses; Information technology; Information technology; Moral and ethical aspects; Professional ethics; dept.phi; faculty_collection

Oedipus: The Most Crucial Concept in Psychoanalysis - Nasio, Juan-David (SUNY series in contemporary French thought, 2010)
In this work, the author argues that the Oedipus complex represents the core of psychoanalysis as well as the fundamental constitution of the human being.--(Source of description unspecified.)
Keywords: Oedipus complex; Psychoanalysis; Oedipus Complex; Psychoanalytic Therapy; dept.phi; faculty_collection

Writing Two Major Chapters of a Book on Flourishing Ethics: Sabbatical Spring 2009 - Bynum, Terrell Ward (2009)
The chapter on the information ethics of Oxford scholar, Luciano Floridi, was completed and is scheduled for publication in Floridi's anthology. The keynote address, Philosophy and the Information Revolution, presented at the Computer Ethics: Philosophical Enquiry 2009 conference in Corfu, Greece, is also scheduled for publication in the journal Ethics and Information Technology. The ideas from both articles have been included in the curriculum for the Computer Ethics class at SCSU.
Keywords: dept.phi; faculty_collection

French Interpretations of Heidegger: An Exceptional Reception - Pettigrew, David; Raffoul, François (SUNY series in contemporary French thought, 2008)
"French Interpretations of Heidegger undertakes a philosophical engagement with the work of the most significant and creative figures involved in the reception of Heidegger in France. The essays address those thinkers who have been influenced by Heidegger's thought and have interpreted it in remarkable ways, including Levinas, Beaufret, Sartre, Merleau-Ponty, Foucault, Derrida, Deleuze, Nancy, Lacoue-Labarthe, Irigaray, Zarader, Greisch, and Dastur. The volume explores the extraordinary impact that Heidegger's thought has had on contemporary French philosophy, including such movements as existentialism, deconstruction, feminist theory, post-structuralism, and hermeneutics, and illustrates its impact on the American continental scene as well."--Jacket.
Keywords: Heidegger, Martin, 1889-1976; Philosophy, French; dept.phi; faculty_collection

Genocide's Aftermath: Responsibility and Repair - Card, Claudia; Marsoobian, Armen (Metaphilosophy series in philosophy, 2007)
Keywords: Genocide; Government policy; Genocide; History; Genocide; Moral and ethical aspects; Genocide; Prevention; dept.phi; faculty_collection

The Creation of the World, or, Globalization - Nancy, Jean-Luc (SUNY series in contemporary French thought, 2007)
"Appearing in English for the first time, Jean-Luc Nancy's 2002 book reflects on globalization and its impact on our being-in-the-world. Developing a contrast in the French language between two terms that are usually synonymous, or that are used interchangeably, namely globalisation (globalization) and mondialisation (world-forming), Nancy undertakes a rethinking of what "world-forming" might mean. At stake in this distinction is for him nothing less than two possible destinies of our humanity, and of our time. This book is an important contribution by Nancy to a philosophical reflection on the phenomenon of globalization and a further development on his earlier works on our being-in-common, justice, and a-theological existence."--Jacket.
Keywords: Globalization; Philosophy; Political science; Philosophy; Teleology; dept.phi; faculty_collection

The Philosophical Challenge of September 11 - Rockmore, Tom; Margolis, Joseph; Marsoobian, Armen (Metaphilosophy series in philosophy, 2005)
Keywords: Philosophy; Philosophy; Political science; September 11 Terrorist Attacks, 2001; Terrorism; United States; Terrorism; dept.phi; faculty_collection

Computer Ethics and Professional Responsibility - Bynum, Terrell Ward; Rogerson, Simon (Blackwell Pub., 2004)
Keywords: Electronic data processing; Moral and ethical aspects; dept.phi; faculty_collection

The Blackwell Guide to American Philosophy - Marsoobian, Armen; Ryder, John (Blackwell philosophy guides, 2004)
Keywords: Philosophy, American; dept.phi; faculty_collection

The Book of Love and Pain: Thinking at the Limit with Freud and Lacan - Nasio, Juan-David (SUNY series in psychoanalysis and culture, 2004)
"In The Book of Love and Pain, Juan-David Nasio offers the first exclusive treatment of psychic pain in Freudian and Lacanian psychoanalytic literature. Using insights gained from more than three decades as a practicing psychoanalyst, Nasio addresses the limits faced by the analyst in attempting to think and treat pain psychoanalytically. He suggests that while pain is about separation and loss, psychic pain is intensified by paradoxical overinvestment in the lost loved one. Included are discussions of the pain of mourning, the pain of jouissance, unconscious pain, pain as an object of the drive, pain as a form of sexuality, pain and the scream, and the pain of silence. In offering a phenomenological description of psychic pain, The Book of Love and Pain fills a gaping void in psychoanalytic research and will play an important role in our understanding of the human psyche. Book jacket."--Jacket.
Keywords: Pain; Psychological aspects; Psychoanalysis; Stress, Psychological; dept.phi; faculty_collection; methods; psychology; Psychoanalytic Theory; Psychoanalytic Therapy; therapy; Bereavement; Pain

Cyberphilosophy: The Intersection of Philosophy and Computing - Moor, James H.; Bynum, Terrell Ward (Blackwell, 2002)
Keywords: Data processing; Philosophy; dept.phi; faculty_collection

Reimagining a Lost Armenian Home: The Dildilian Photography Collection - Marsoobian, Armen (I.B. Tauris, 2017)
For nearly a century members of the Dildilian family practiced the art of photography in Ottoman Turkey, Greece and the United States. This book contains over 200 photographs, primarily from the Ottoman era, beginning with the creation of the family business by Tsolag Dildilian in Sivas in central Turkey in 1882 and concluding in 1922 in Samsun, when the family was forced into exile in Greece. The photographs and the stories that unfold around them capture a defining period in the nearly three thousand year history of the Armenians in Anatolia and the Armenian Highlands. The early-twentieth century witnessed the violent erasure of the Armenians from their historic homeland, with catastrophic effects for the Dildilian family and their community. Yet this was also a period of unprecedented educational, cultural and commercial development for the Armenians. The Dildilian family was intimately involved in the triumphs and tragedies of these years and this book, through its rich pictorial history, sheds unprecedented light on the real-life experiences of Armenians in the devastating years of the Armenian Genocide and beyond. It is an unusual and original contribution to the social history of the Near East.
Keywords: Dildilian family; Armenians; Pictorial works; Portraits; Armenia; dept.phi; faculty_collection

Heidegger in France - Janicaud, Dominique (Studies in Continental thought, 2015)
Dominique Janicaud claimed that every French intellectual movement--from existentialism to psychoanalysis--was influenced by Martin Heidegger. This translation of Janicaud's landmark work, Heidegger en France, details Heidegger's reception in philosophy and other humanistic and social science disciplines. Interviews with key French thinkers such as Françoise Dastur, Jacques Derrida, Éliane Escoubas, Jean Greisch, Philippe Lacoue-Labarthe, Jean-Luc Marion, and Jean-Luc Nancy are included and provide further reflection on Heidegger's relationship to French philosophy. An intellectual undertaking of authoritative scope, this work furnishes a thorough history of the French reception of Heidegger's thought.--Publisher website.
Keywords: 20th century; Philosophers; France; Heidegger, Martin, 1889-1976; Philosophy, French; Interviews; dept.phi; faculty_collection

Fragments of a Lost Homeland: Remembering Armenia - Marsoobian, Armen (I.B. Tauris & Co. Ltd., 2015)
Keywords: 1801-1900; Dildilian family; Armenian Genocide, 1915-1923; History; Personal narratives, Armenian; Armenian Genocide, 1915-1923; Armenia; SCSU Faculty Scholar Award; award_winner; dept.phi; faculty_collection

Heidegger and Practical Philosophy - Raffoul, François; Pettigrew, David (SUNY series in contemporary continental philosophy, 2002)
Investigating the extent to which Heidegger's thought can be read as a crucial resource for practical philosophy and the articulation of an ethos for our time, leading scholars offer a sustained and intensive focus on Heidegger's thought of praxis.--(Source of description unspecified.)
Keywords: Heidegger, Martin, 1889-1976; Ethics; Political science; Philosophy; Practice (Philosophy); dept.phi; faculty_collection

Why Controlling the Historical Narrative Matters: A Jamesian Response - Marsoobian, A.T. (Pragmatism Today, 2022)
An examination of the lessons learned from William James’s oration on the dedication of the Civil War Monument memorialization Colonel Robert Shaw and the Fifty-Fourth Regiment Massachusetts Infantry, an all-Black unit. The role of monuments in making visible the values of a society is explored in the context of promoting a nation’s historical narrative, in particular in their propagation of the South’s Lost Cause narrative. The genocidal violence against Armenians in the Caucasus by the Azerbaijani regime serves as the second illustration of the abuse of historical narratives. © 2022 Central European Pragmatist Forum. All rights reserved.
Keywords: Armenians; Azerbaijan; Civil War monuments; William James; civic courage; dept.phi; genocidal violence; historical narratives; peer-reviewed; the Lost Cause; ⛔ No DOI found

Ai moral enhancement: upgrading the socio-technical system of moral engagement - Volkman, Richard; Gabriels, Katleen (Science and Engineering Ethics, 2023)
Several proposals for moral enhancement would use AI to augment (auxiliary enhancement) or even supplant (exhaustive enhancement) human moral reasoning or judgment. Exhaustive enhancement proposals conceive AI as some self-contained oracle whose superiority to our own moral abilities is manifest in its ability to reliably deliver the ‘right’ answers to all our moral problems. We think this is a mistaken way to frame the project, as it presumes that we already know many things that we are still in the process of working out, and reflecting on this fact reveals challenges even for auxiliary proposals that eschew the oracular approach. We argue there is nonetheless a substantial role that ‘AI mentors’ could play in our moral education and training. Expanding on the idea of an AI Socratic Interlocutor, we propose a modular system of multiple AI interlocutors with their own distinct points of view reflecting their training in a diversity of concrete wisdom traditions. This approach minimizes any risk of moral disengagement, while the existence of multiple modules from a diversity of traditions ensures pluralism is preserved. We conclude with reflections on how all this relates to the broader notion of moral transcendence implicated in the project of AI moral enhancement, contending it is precisely the whole concrete socio-technical system of moral engagement that we need to model if we are to pursue moral enhancement.
Keywords: AI socratic interlocutor; Artificial intelligence; Artificial moral agent; Moral enhancement; dept.phi; peer-reviewed

Ethics and Information Technology: Guest editor's introduction - Bynum, T.W. (Ethics and Information Technology, 2001)
Keywords: Information technology; Social sciences; dept.phi

Transformation in Deleuze and Heidegger: Serial and thematic repetition - Gilliland, R. (Philosophy Today, 2005)
Keywords: dept.phi

Probability and Tempered Modal Eliminativism - Shaffer, M.J. (History and Philosophy of Logic, 2004)
In this paper the strategy for the eliminative reduction of the alethic modalities suggested by John Venn is outlined and it is shown to anticipate certain related contemporary empiricistic and nominalistic projects. Venn attempted to reduce the alethic modalities to probabilities, and thus suggested a promising solution to the nagging issue of the inclusion of modal statements in empiricistic philosophical systems. However, despite the promise that this suggestion held for laying the ‘ghost of modality’ to rest, this general approach, tempered modal eliminativism, is shown to be inadequate for that task. © 2004 Taylor & Francis Group, LLC.
Keywords: dept.phi

Daniel Dennett and the computational turn - Dorbolo, J.; Barnette, R.; Bynum, T.; Cavalier, R.; Moor, J.; Rosenthal, D.M.; Uzgalis, B. (Minds and Machines, 2006)
Keywords: dept.phi

Norbert wiener and the rise of information ethics - Bynum, T.W. (Information Technology and Moral Philosophy, 2008)
To live effectively is to live with adequate information. Thus, communication and control belong to the essence of man's inner life, even as they belong to his life in society. Norbert Wiener SCIENCE, TECHNOLOGY, AND ETHICS. Major scientific and technological innovations often have profound social and ethical effects. For example, in Europe during the sixteenth and seventeenth centuries, Copernicus, Newton, and other scientists developed a powerful new model of the universe. This stunning scientific achievement led to increased respect for science and for the power of human reasoning. During that same era, recently invented printing-press technology made it possible to spread knowledge far and wide across Europe, instead of leaving it, as before, in the hands of a privileged minority of scholars. Inspired by these scientific and technological achievements, philosophers, such as Hobbes, Locke, and Rousseau, re-examined human nature and the idea of a good society. They viewed human beings asrational agentscapable of thinking for themselves and acquiring knowledge through science and books. In addition, they interpreted society as a creation of informed, rational citizens working together throughsocial contracts. These philosophical developments laid foundations for ethical theories such as those of Bentham and Kant, and for political changes such as the American Revolution and the French Revolution. Today, after far-reaching scientific achievements in physics, biology, and cybernetics – and after recent technological advances in digital computing and information networks – philosophers are again rethinking the nature of human beings and of society. © Cambridge University Press 2008 and 2009.
Keywords: dept.phi

Response to Frisina's response - Yang, X. (Dao, 2009)
Keywords: dept.phi; peer-reviewed

Pornography As Simulation - Bach, T. (Porn - Philosophy for Everyone, 2010)
Keywords: Folk-psychological prowess, on MTV's The Hills; Mental simulation, and the "off-line" heuristic; Modern perversion of mental simulation; Money, lesbians and woodsmen; Philosophers and psychologists, "theory-theory" approach to folk psychology; Pornography as simulation; Simulating a day at the office; Tools of folk psychology-human beings, are prolific psychologists; World of actual sexual relationships-dangerous sexually transmitted diseases, more lethal than ever; dept.phi; origin of simulation-pornographic appropriation of mind-reading skill, and mentalizing ability

Foreword - Bynum, T.W. (Ethical Issues and Social Dilemmas in Knowledge Management: Organizational Innovation, 2010)
Keywords: dept.phi

Jokers on the mountain: In defense of gratuitous risk - Lockwood, H.H. (Climbing - Philos. for Everyone: Because It's There, 2010)
Keywords: "Jokers on the Mountain"; "The Outside Prognosticator: Really Quite Stupid"; Dan Osman's new game of controlled falling as a "Stupid Pastime"; Maria Coffey's book, Where the Mountain Casts Its Shadow; Mountaineering: The Freedom of the Hills; The Rule of Rescue; The predecessor of the so-called "Beacon Bill"; dept.phi

Federative Global Democracy - Cavallero, E. (Global Democracy and Exclusion, 2011)
Keywords: Allocation of sovereign competences - over territorial jurisdictions; Exercise of sovereign competences, at every level - constrained by effective global human rights regime; Federative global democracy; Global Federative Model and State sovereignty - internal and external aspects; Global federative model and its aims - avoiding concentration of sovereign powers in territorial jurisdiction; Gould, defending second principle of political inclusion - ground rights of participation; Internal sovereignty, exclusive, irrevocable legal competence - making policy to govern; Internalization condition, external costs internalized - through constitution of composite polities; Local democratic institutions - and global ones; Polity's legal competence, sovereign - exclusive and irrevocable for territory; dept.phi

Do Differences in Grammatical Form between Languages Explain Differences in Ontology between Different Philosophical Traditions?: A Critique of the Mass-Noun Hypothesis - Yang, X. (Dao, 2011)
It is an assumed view in Chinese philosophy that the grammatical differences between English or Indo-European languages and classical Chinese explain some of the differences between the Western and Chinese philosophical discourses. Although some philosophers have expressed doubts about the general link between classical Chinese philosophy and syntactic form of classical Chinese, I discuss a specific hypothesis, i. e., the mass-noun hypothesis, in this essay. The mass-noun hypothesis assumes that a linguistic distinction such as between the singular terms and the predicates is sufficient to justify or necessarily leads to a specific ontological distinction such as the distinction between the particular and the universal. I argue that one cannot read off semantic properties simply from syntactic ones and hence the syntactic differences do not automatically translate into the semantic differences between languages, that the syntactic features of Chinese nouns do not have explanatory significance in explaining why the particular-universal problem does not arise in the classical period of Chinese philosophy, and that the part-whole ontology allegedly informed by the mass-noun-like semantics does not provide a natural or intuitive picture of the language-world relation. © Springer Science+Business Media B.V.2011.
Keywords: Mass noun and count noun; Ontology; Syntactic and semantic distinction; dept.phi; peer-reviewed

Two self-critiques in Heidegger's critique of metaphysics - Gilliland, R. (Journal of Speculative Philosophy, 2012)
This article traces shifts in Heidegger's stance toward metaphysics after fundamental ontology and argues that these shifts reflect changes in his conceptions of ontological difference and temporality that pave the way for his mature thought. Copyright © 2012 The Pennsylvania State University.
Keywords: dept.phi; ⚠️ Invalid DOI

A psychoanalyst on the couch - Nasio, J.-D.; Raffoul, F.; Pettigrew, D. (A Psychoanalyst on the Couch, 2012)
An interview with Juan-David Nasio. In A Psychoanalyst on the Couch, we find the noted psychoanalyst and Lacan commentator Juan-David Nasio on the analyst's couch himself. In the interview that makes up this book, he provides insight into his forty-year career as a writer and practitioner, elaborating on Freudian and Lacanian concepts important to his work and reflecting on broad issues related to psychology and culture-as well as personal remembrances. The result is an intimate and wide-ranging look at the man and thinker, both an introduction to his work and a deeper look at his approach and outlook. © 2012 State University of New York. All rights reserved.
Keywords: dept.phi

The task of justice - Pettigrew, D. (Jean-Luc Nancy and Plural Thinking: Expositions of World, Ontology, Politics, and Sense, 2012)
Keywords: dept.phi

Roman Catholic monasticism in Poland: A brief overview of selected issues - Górniak-Kocikowska, K. (Monasticism in Eastern Europe and the Former Soviet Republics, 2015)
Keywords: dept.phi

In defense of the critical philosophy: On Schelling's departure from Kant and Fichte in Abhandlungen zur Erläuterung des Idealismus der Wissenschaftslehre (1796/1797) - Harry, C.C. (Journal of Speculative Philosophy, 2015)
This article considers the second treatise of Schelling's Abhandlungen zur Erläuterung des Idealismus der Wissenschaftslehre (Treatises Explaining the Idealism of the Science of Knowledge, 1796/97), a lesser-known work from the early Schelling. Here, Schelling proposes to defend the critical position insofar as it purports to be a system based on human reason, but instead he issues a backhanded critique of the assumption on behalf of the critical philosophers to try and limit the bounds of pure reason by means of their own use of reason. Schelling then offers an alternative way to think about the relationship of mind (Geist) and matter in nature. This article argues that Schelling's actual explanation of the critical philosophy as a position founded by reasonable minds ultimately belies his promise to defend it, thus calling into question that Schelling's thought prior to 1800 was a mere reiteration of Kantian/Fichtean transcendentalism. Copyright © 2015 The Pennsylvania State University, University Park, PA.
Keywords: Critical philosophy; Fichte; Kant; Naturphilosophie; Shelling; dept.phi

On the fundamental dissimilarity of aristotelian and Kantian time concepts - Harry, C.C. (Idealistic Studies, 2015)
In Aristotle's Physics iv 10-14, Aristotle argues for a time concept derived with, on a weak version, sense perception, and, on a strong version, from sense perception along with intellection (nous), from change in nature. On both accounts, actualized time for Aristotle requires cognitive faculties. Aristotle's time concept has thus been linked with Kant's treatment of time in the Transcendental Aesthetic of his First Critique. More importantly, the conclusion that time is "unreal" for Aristotle elicits charges of adulterating Aristotle's conclusions by reading Aristotle's Physics with a Kantian lens. In this paper, I examine the context of Kant's conclusions about time and, by way of a contrast between the Aristotelian and Kantian projects, argue for a fundamental dissimilarity of their accounts. And yet, I reserve the possibility that one both ascent to this fundamental dissimilarity and hold that Aristotle was not a temporal realist. © 2015. Idealistic Studies.
Keywords: dept.phi; peer-reviewed

Taking Time - Harry, C.C. (SpringerBrief. Philos., 2015)
Despite the language we saw in the previous chapter, which allowed for time apprehension by perception and marking, in Physics iv 14, Aristotle famously argues that time is dependent on nous. © 2015, The Author(s).
Keywords: Human Child; Nonhuman Animal; Pure Actuality; Sense Perception; Time Perception; dept.phi

The Armenian Genocide of 1915: Armen T. Marsoobian explores the complex history of one of the 20th-century's worst and most neglected crimes against humanity - Marsoobian, A.T. (History Today, 2015)
Keywords: dept.phi; ⛔ No DOI found

The task of justice - Pettigrew, D. (Pathways to Reconciliation: Between Theory and Practice, 2016)
Contemporary discourse about human rights makes pragmatic use of the 1948 United Nations Universal Declaration on Human Rights, as the Declaration presents a set of guidelines that are based on assumptions about the nature of human beings: Their thoughts, ideas, freedom of expression and freedom of association.1 Article 1 of the Declaration states, for example, that ‘All human beings are born free and equal in dignity and rights. They are endowed with reason and conscience and should act towards one another in a spirit of brotherhood.’ The document engages the idea of the human being as having rights, regardless of ethnicity or gender. Such rights include life, protection from harm, and access to the latest in scientific technology.2 © Philipa Rothfield, Cleo Fleming and Paul A. Komesaroff 2008.
Keywords: dept.phi

Virtues, vices, and situations: What warrants the ascription of character traits - Yang, X. (Journal of Theoretical and Philosophical Psychology, 2016)
In recent years, situationism in psychology has caught the attention of philosophers. Some have defended it. Some have argued against it. The situationist has challenged the traditional view shared by personality psychology and virtue ethics that people differ in terms of character or character traits and that we can explain and predict people's behavior by character traits people have. Previous responses to situationism try to show that experiments from social psychology do not undermine the traditional view. I agree and will further argue that the fact that experiments do not undermine the traditional view is not sufficient to warrant the attribution of character traits, and that some philosophical arguments are needed given that not enough empirical data that show a high degree of behavioral consistencies are available. I first offer an account of the ordinary attribution of character traits according to which having character traits is a matter of degree, and argue that the ordinary attribution account comes from the Aristotelian moral psychology and is consistent with a long-standing tradition, the trait paradigm, in personality psychology. Second, I argue that although situational factors play some role in explaining and predicting behavior, the attribution of character traits plays a primary and indispensable role. Third, I argue that ordinary attribution of character traits has important functions in our moral life, which cannot be fulfilled by the attribution of local traits suggested by the situationist. I also argue that the ethical management of situations recommended by the situationist can help in getting things right, but is not sufficient to be the adequate foundation for our normative discourse. © 2016 American Psychological Association.
Keywords: Attribution of character traits; Crosssituational consistency and variation; Local traits; Situationism; Virtues; dept.phi

The computer revolution and the problem of global ethics - Gorniak-Kocikowska, K. (Computer Ethics, 2017)
The author agrees with James Moor that computer technology, because it is 'logically malleable', is bringing about a genuine social revolution. Moor compares the computer reVolution to the 'industrial revolution' of the late 18th and the 19th centuries; but it is argued here that a better comparison is with the 'printing press revolution' that occurred two centuries before that. Just as the major ethical theories of Bentham and Kant were developed in response to the printing press revolution, so a new ethical theory is likely to emerge from computer ethics in response to the computer revolution. The newly emerging field of information ethics, therefore, is much more important than even its founders and advocates believe. © John Weckert 2007. All rights reserved.
Keywords: Computer ethics; Computer revolution; Global ethics; Industrial revolution; Printing revolution; Professional ethics; dept.phi

Editors' Introduction - Lindert, J.; Marsoobian, A.T. (Multidiscipl. Perspect. on Genocide and Memory, 2018)
Keywords: dept.phi

The social self and social death: Rethinking reparations for genocide and crimes against humanity - Marsoobian, A.T. (Pragmatism Today, 2020)
Based on a pragmatist inspired conception of the social self, the concept of reparations for the harms of genocide is reexamined. Both Raphael Lemkin, the person who invented the term “genocide,” and Claudia Card, a philosopher who examined the evil of genocide, hold similarly expansive notions of the harms inflicted by genocidal violence. Both argued that biological death is not necessarily central to genocide. For Lemkin cultural destruction of the targeted group is just as essential as the actual killing itself. Genocide is a group crime that aims to destroy the group and all the social aspects of group identity. Card similarly sees the target of genocidal violence as the social vitality of the self. This vitality is sustained by group relations. Reparations thus need to be reconceptualize in terms of the restoration of social life of the victim group and not solely on the basis of economic losses. Examples are given for the reparation of the social vitality of communities that have suffered genocide. © 2020 Central European Pragmatist Forum. All rights reserved.
Keywords: Claudia Card; Genocide; Raphael Lemkin; Reparations; Social death; Social self; dept.phi; peer-reviewed; ⛔ No DOI found

Global ethics for the digital age – flourishing ethics - Kantar, N.; Bynum, T.W. (Journal of Information, Communication and Ethics in Society, 2021)
Purpose: The purpose of this paper is to explore an emerging ethical theory for the Digital Age – Flourishing Ethics – which will likely be applicable in many different cultures worldwide, addressing not only human concerns but also activities, decisions and consequences of robots, cyborgs, artificially intelligent agents and other new digital technologies. Design/methodology/approach: In the past, a number of influential ethical theories in Western philosophy have focused upon choice and autonomy, or pleasure and pain or fairness and justice. These are important ethical concepts, but we consider “flourishing” to be a broader “umbrella concept” under which all of the above ideas can be included, plus additional ethical ideas from cultures in other regions of the world (for example, Buddhist, Muslim, Confucianist cultures and others). Before explaining the applied approach, this study discusses relevant ideas of four example thinkers who emphasize flourishing in their ethics writings: Aristotle, Norbert Wiener, James Moor and Simon Rogerson. Findings: Flourishing Ethics is not a single ethical theory. It is “an approach,” a “family” of similar ethical theories which can be successfully applied to humans in many different cultures, as well as to non-human agents arising from new digital technologies. Originality/value: This appears to be the first extended analysis of the emerging flourishing ethics “family” of theories. © 2021, Emerald Publishing Limited.
Keywords: dept.phi; peer-reviewed

Guest Editor's introduction. - Bynum, Terrell (Ethics and Information Technology, 2001)
Keywords: dept.phi; ❓ Multiple DOI

The roman catholic church in poland after the fall of communism - Gorniak-Kocikowska, Krystyna (Occasional Papers on Religion in Eastern Europe, 2020)
Keywords: dept.phi; peer-reviewed; ⛔ No DOI found

Nature, Ethics and Gender in German Romanticism and Idealism - Harry, Chelsea C. (Idealistic Studies, 2020)
Keywords: dept.phi; peer-reviewed

The problem of evil in the Neo-Confucian context: Wang Yangming’s view on evil - Yang, Xiaomei (Asian Philosophy, 2020)
Wang Yangming believes that human nature is entirely good. A question naturally arises: where is evil from? It has been argued that Wang’s idealism gives rise to the problem of evil. I first argue that the difficulty for Wang to have a coherent account of evil can be removed when his idealism is understood in a narrow sense. Second, I offer an account of Wang’s view on evil in three steps. First, I argue that evil comes from the interaction between humans and the external world according to Wang. Second, I show that given Wang’s account of human nature with three aspects, there is no contradiction between Wang’s claim that human nature is the same in everyone and Wang’s claim about differences in our natural endowment which affect our moral practice. Third, I argue that Wang’s doctrine of non-distinction of good and evil in the original substance of human nature is uniquely Confucian. © 2020 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Human nature; dept.phi; idealism; origin of evil; peer-reviewed; physical nature

Breaking the silence: Memorialization and cultural repair in the aftermath of the armenian genocide - Marsoobian, Armen T. (Mass Violence and Memory in the Digital Age, 2020)
Keywords: dept.phi

Ethical challenges to citizens of ‘The automatic Age’: Norbert Wiener on the information society - Bynum, Terrell Ward (Journal of Information, Communication and Ethics in Society, 2004)
This article discusses the foresight of philosopher/mathematician Norbert Wiener who, in the 1940s, founded Information Ethics as a research discipline. Wiener envisioned the coming of an “automatic age” in which information technology would have profound social and ethical impacts upon the world. He predicted, for example, machines that will learn, reason and play games; “automatic factories” that will replace assembly-line workers and middle managers with computerized devices; workers who will perform their jobs over great distances with the aid of new communication technologies; and people who will gain remarkable powers by adding computerized “prostheses” to their bodies. To analyze the ethical implications of such developments, Wiener presented some principles of justice and employed a powerful practical method of ethical analysis. © 2004, Emerald Group Publishing Limited
Keywords: Human purposes; Information ethics; Justice; dept.phi; peer-reviewed

Privacy as life, liberty, property - Volkman, Richard (Ethics and Information Technology, 2003)
The cluster of concerns usually identified as matters of privacy can be adequately accounted for by unpacking our natural rights to life, liberty, and property. Privacy as derived from fundamental natural rights to life, liberty, and property encompasses the advantages of the control and restricted access theories without their attendant difficulties., (C)2003 Kluwer Academic Publishers
Keywords: Access control; Data privacy; Information technology; Judith Thomson; Natural rights; Privacy; Right to privacies; Right to privacy; Social sciences; Thomson; dept.phi; natural rights; privacy; right to privacy

Introduction to cyberphilosophy - Moor, James H.; Bynum, Terrell Ward (Metaphilosophy, 2002)
Keywords: dept.phi

Computer ethics: Its birth and its future - Bynum, Terrell Ward (Ethics and Information Technology, 2001)
This article discusses some "historical milestones" in computer ethics, as well as two alternative visions of the future of computer ethics. Topics include the impressive foundation for computer ethics laid down by Norbert Wiener in the 1940s and early 1950s; the pioneering efforts of Donn Parker, Joseph Weizenbaum and Walter Maner in the 1970s; Krystyna Gorniak's hypothesis that computer ethics will evolve into "global ethics"; and Deborah Johnson's speculation that computer ethics may someday "disappear"., (C)2001 Kluwer Academic Publishers
Keywords: Applied ethics; Computer ethics; Cybernetics; Global ethics; Information ethics; Information technology; Philosophical aspects; Professional responsibilities; Professional responsibility; Social sciences; applied ethics; computer ethics; cybernetics; dept.phi; global ethics; information ethics; professional responsibility; ❓ Multiple DOI

The challenge of applying ethics. - Bynum, Terrell Ward (Science and Engineering Ethics, 2001)
Keywords: *Computers; *Ethics; Computers; Ethics; Humans; article; computer; dept.phi; ethics; human

Revolution and the library - Gorniak-Kocikowska, K (Library Trends, 2001)
The focus of this article is primarily on the impact that the computer revolution has on college/university libraries, although many of the issues discussed here are relevant to other types of libraries as well. The university library in its present form is a product of the printing press revolution. In all likelihood, the computer revolution will have an even more profound impact on the library than did the printing press revolution.
Keywords: dept.phi; ⛔ No DOI found

Special section on computer ethics - Bynum, Terrell Ward (Science and Engineering Ethics, 2000)
Keywords: dept.phi

The foundation of computer ethics - Bynum, Terrell Ward (ACM Sigcas Computers and Society, 2000)
Keywords: dept.phi

Milestones in the History of Information and Computer Ethics - Bynum, Terrell Ward (The Handbook of Information and Computer Ethics, 2009)
This chapter contains sections titled: Introduction Norbert Wiener's Foundation of Information Ethics Computer Ethics Developments after Wiener and before Maner Walter Maner's Computer Ethics Initiative Deborah Johnson's Influential Textbook and the Start of the “Uniqueness Debate” James Moor's Classic Paper and His Influential Computer Ethics Theory The Professional-Ethics Approach of Donald Gotterbarn Computing and Human Values Luciano Floridi's Information Ethics Theory Concluding Remarks: The Exponential Growth of Computer Ethics References and Selected Resources
Keywords: Computer ethics developments - after Wiener and before Maner; Donald Gotterbarn professional-ethics approach; Information and computer ethics - milestones in history; computer ethics developments - after Wiener and before Maner; dept.phi; information and computer ethics - milestones in history

Federative Global Democracy - Cavallero, Eric (Metaphilosophy, 2009)
Abstract: In this essay a set of principles is defended that yields a determinate allocation of sovereign competences across a global system of territorially nested jurisdictions. All local sovereign competences are constrained by a universal, justiciable human rights regime that also incorporates a conception of cross-border distributive justice and regulates the competence to control immigration for a given territory. Subject to human rights constraints, sovereign competences are allocated according to a conception of global democracy. The proposed allocation scheme can accommodate substantial local autonomy while at the same time ensuring that everyone has a voice in the political decisions that affect his or her interests. The relevant class of affected interests is fully specified. Relevant affects are of two kinds: those that impose norms of governance on individuals, and those that impose external costs on them. The favored sense of “an external cost” is developed and defended.
Keywords: Affected interests; All-affected principle; Borders; Confederalism; Democracy; Democratic deficit; Equal protection; External costs; Externalities; Federalism; Global governance; Global justice; Globalization; Human rights; Immigration; International law; affected interests; all-affected principle; borders; confederalism; democracy; democratic deficit; dept.phi; equal protection; external costs; externalities; federalism; global governance; global justice; globalization; human rights; immigration; international law; nationalism; sovereignty; territoriality

Acknowledging intergenerational moral responsibility in the aftermath of genocide - Marsoobian, Armen T (Genocide Studies and Prevention, 2009)
Keywords: dept.phi

How to make sense of the claim “True knowledge is what constitutes action”: A new interpretation of wang yangming’s doctrine of unity of knowledge and action - Yang, Xiaomei (Dao-a Journal of Comparative Philosophy, 2009)
No one denies the importance of applying knowledge to actions. But claiming identity (unity) of knowledge and action is quite another thing. There seem to be two problems with the claim: (1) the identity claim implies that the sole cause for one to fail to act on what one judges to be right is ignorance, but it is obviously false that the sole cause of failure in moral actions is ignorance. (2) The identity statement implies non-separation of knowledge and action. But knowledge does not necessarily lead to action. However, the identity of knowledge and action is what a famous Ming Confucian scholar, Wang Yang-ming, proposed and the concept became the central doctrine of his teaching. Though there are several major interpretations of Wang's doctrine in contemporary literature, it is not clear to me how they deal with the above mentioned difficulties. In this article, I will discuss these interpretations of the doctrine and propose a new interpretation. My purpose is to give an interpretation of Wang's doctrine that has the capacity of dealing with these challenges to the doctrine and also captures the essence of his teaching. © 2009 Springer Science+Business Media B.V.
Keywords: Action; Chinese philosophy; Moral knowledge (liang zhi); Neo-confucianism; dept.phi; peer-reviewed

ICT and the tension between old and new: the human factor - Gorniak-Kocikowska, Krystyna (Journal of Information, Communication and Ethics in Society, 2008)
Purpose The purpose of this paper is to deepen the understanding of tensions between old and new in the emerging global society driven by information and communication technology (ICT); and to argue that creation of a theory of this society would contribute in the easing of these tensions. Design/methodology/approach The methods used in this paper are mostly analytical, descriptive, and qualitative. An analysis of the creation and development of ICT from a mathematical discipline of computer science to a universal tool and a driving force of the emerging global society, a development which is paralleled by the commercialization of ICT, is followed by two case studies illustrating the tensions between old and new and the role ICT plays in them. One case is centered on the challenges of traditional models of education by new, ICT-friendly approaches, like the Multiple Intelligences Theory; the other addresses tensions between old and new that in many societies presently take the form of tensions between local/national and global. Findings A claim is formed that the existing tensions between old and new are closely linked to the tensions between the two most common forms of society, inclusive (egalitarian) and exclusive (elitist). Originality/value The paper will help understand some of the reactions to the process of globalization. It can serve as a tool for assessment and prediction regarding this process. Lastly, the paper contains a justification of merit in the creation of a “grass root” theory of an ICT-driven global society built on a universally accepted ethical foundation. © 2008, Emerald Group Publishing Limited
Keywords: Communication technologies; Education; Ethics; Globalization; Information society; Language; dept.phi; peer-reviewed

Some issues in Chinese philosophy of religion - Yang, Xiaomei (Philosophy Compass, 2008)
Keywords: dept.phi

Casuistry and computer ethics - Coleman, Kari Gwen (Metaphilosophy, 2007)
At the heart of the uniqueness debate is the possibility that the computer revolution may demand more in the way of ethical analysis than our traditional (that is, modern) ethical edification has prepared us for. In short, it may present new and unique problems and therefore demand new and unique solutions. In this article I argue that the solution is in fact an old and not-sounique one: casuistry. Appealing to Jonsen and Toulmin's analysis of casuistry (1988), I argue that a casuistic methodology is a more accurate description of the moral reasoning used by contemporary computer ethicists than are other accounts. In addition, I argue that the strengths that enabled casuistry to deal successfully with radical social, economic, and religious changes in the sixteenth and seventeenth centuries render casuistry well suited to the task of dealing with radically new situations like those found in twentieth- and twenty-first-century computer technology. Before concluding, I briefly explore Pascal's fatal critique of casuistry and its relevance for contemporary computer ethics. © 2007 Metaphilosophy LLC and Blackwell Publishing Ltd.
Keywords: Casuistry; Computer ethics; Information ethics; Methodology; Moral reasoning; Uniqueness debate; dept.phi

From computer ethics to the ethics of global ICT society - Gorniak-Kocikowska, Krystyna (Library Hi Tech, 2007)
Purpose - The purpose of this paper is to address the place of computer/ICT ethics in the global ICT society driven by knowledge economy. Design/methodology/approach - The paper focuses on three main issues: the evolution of the name of the leading technology of our times and, accordingly, the evolution of the name of the society in which this technology plays the leading role; some ethical dilemmas that the global ICT society will need to solve; global ICT ethics and the knowledge economy. Findings - The paper suggests that global ICT ethics should be an ethics focusing on the dynamics of the relationship between the weak and the strong, the rich and the poor, the healthy and the sick worldwide - and it should explore the ethical problems from the point of view of both parties involved. That way, Global ICT Ethics can have a truly communicative character, and it can become an ethics that will be both a co-creator and also a result of a democratic processes. Originality/value - This paper should interest anyone concerned with ICT and globalization.
Keywords: Communication technologies; Ethics; Globalization; dept.phi; peer-reviewed

Flourishing ethics - Bynum, Terrell Ward (Ethics and Information Technology, 2006)
This essay describes a new ethical theory that has begun to coalesce from the works of several scholars in the international computer ethics community. I call the new theory Flourishing Ethics because of its Aristotelian roots, though it also includes ideas suggestive of Taoism and Buddhism. In spite of its roots in ancient ethical theories, Flourishing Ethics is informed and grounded by recent scientific insights into the nature of living things, human nature and the fundamental nature of the universe-ideas from today's information theory, astrophysics and genetics. Flourishing Ethics can be divided conveniently into two parts. The first part, which I call Human-Centered FE, is focused exclusively upon human beings - their actions, values and characters. The second part, which I call General FE, applies to every physical entity in the universe, including humans. Rather than replacing traditional great ethical theories, Flourishing Ethics is likely to deepen and broaden our understanding of them. © Springer Science+Business Media B.V. 2006.
Keywords: Aristotelian ethics; Astrophysics; Computer ethics; Cybernetics; Cyborg ethics; Entropy; Good and evil; Information ethics; Infosphere; Just consequentialism; Philosophical aspects; Robot ethics; dept.phi

Introduction: genocide's aftermath - Card, Claudia; Marsoobian, Armen T (Metaphilosophy, 2006)
Keywords: dept.phi

Dynamic traditions: why globalization does not mean homogenization - Volkman, Richard (Journal of Information, Communication and Ethics in Society, 2006)
In light of the relation between culture and markets, an analysis of cultural evolution reveals that globalization will not lead to the homogenization of world cultures. © 2006, Emerald Group Publishing Limited
Keywords: Culture; Globalization; Market; Tradition; dept.phi; peer-reviewed

The Armenian genocide in film: overcoming denial and loss - Marsoobian, Armen T (The history of genocide in cinema: atrocities on screen, 2017)
Keywords: dept.phi

Cinematic witnessing of the genocide in Bosnia 1992–1995: toward a poetics of responsibility - Pettigrew, David (The history of genocide in cinema: atrocities on screen, 2017)
Keywords: dept.phi

Mandate interrupted: the problematic legacy of the international criminal tribunal for the former Yugoslavia - Pettigrew, David (Washington University Global Studies Law Review, 2020)
Keywords: dept.phi; ⛔ No DOI found

False friends and false coinage: a tool for navigating the ethics of sociable robots - Elder, Alexis (ACM Sigcas Computers and Society, 2016)
Keywords: dept.phi

The Factor of Listening in Karl Jaspers’ Philosophy of Communication - Górniak-Kocikowska, Krystyna (Philosophical Faith and the Future of Humanity, 2012)
Jaspers’ views on communication and his approach to the question of listening, both underwent an evolution in which World War II and the first years thereafter played a crucial role. In this process, Jaspers journeyed from listening to the great minds of the past, through an inward dialogue with them, to one-sided lecturing while his audience was engaged in a straight-line listening, to an intimate dialogue with those he considered like-minded, to a multi-faceted dialogue, and finally to listening to his contemporaries and learning how to practice transactional listening-in-conversation in the process of a multi-layered communication he called a loving struggle. This evolution, paralleled by the transition of Japers’ philosophy from local-centered to world-centered makes his thinking attractive and useful today.
Keywords: German Student; Great Mind; Nazi Regime; Political Involvement; Verbal Communication; dept.phi

Knowledge management and democracy: A critical review of some moral issues and social dilemmas - Gorniak-Kocikowska, K (Organizational Learning and Knowledge: Concepts, Methodologies, Tools and Applications, 2011)
The main problem discussed in this chapter is the question of compatibility between knowledge management in the knowledge economy and democracy in the ICT-driven global society. The assumption is made that democracy is the dominant form of organizing the global society on a variety of levels; and that it is regarded as desirable and morally superior in comparison with other such forms. © 2011, IGI Global.
Keywords: dept.phi

The eclipse and rebirth of american philosophical pluralism: a history lesson about his-tory - Marsoobian, Armen T (Wisdom, 2016)
Keywords: dept.phi

The path dependence of dynamic traditions and the illusion of cultural AIDS - Volkman, Richard (ACM Sigcas Computers and Society, 2016)
Keywords: dept.phi

Computer ethics beyond mere compliance - Volkman, Richard (Journal of Information, Communication and Ethics in Society, 2015)
Purpose – The paper aims to examine the nature of computer ethics as a field of study in light of 20 years of Ethicomp, arguing that computer ethics beyond mere compliance will have to be pluralistic and sensitive to the starting places of various audiences. Design/methodology/approach – The essay offers a philosophical rather than empirical analysis, but the ideal of open inquiry is observed to be manifest in the practice of Ethicomp. Findings – If computer ethics is to constitute a real engagement with industry and society that cultivates a genuine sensitivity to ethical concerns in the creation, development and implementation of technologies, a genuine sensitivity that stands in marked contrast to ethics as “mere compliance”, then computer ethics will have to persist in issuing an open invitation to inquiry. Originality/value – The celebration of 20 years of Ethicomp is an occasion to reflect on who we are and what we mean to be doing. Inclusive of previous accounts (e.g. Moor and Gotterbarn), while going beyond them, an inquiry-based conception of computer ethics makes room for all the various dimensions of computer ethics. ©Emerald Group Publishing Limited
Keywords: Collaboration; Community evolution; Computer ethics; Information ethics; Philosophy; Teaching innovations; dept.phi; peer-reviewed

Physics iv 10-11 as a Parallel Account - Harry, Chelsea C. (Chronos in Aristotle’s Physics: On the Nature of Time, 2015)
Given the context of the Physics just explored, it will not be a surprise if time (chrόnos) in Aristotle’s analytic of time turns out to be not a being qua itself but an attribute of motion, an interval.
Keywords: Infinite Divisibility; Infinite Time; Internal Inconsistency; Natural Object; Underlying Unity; dept.phi

Time in Context - Harry, Chelsea C. (Chronos in Aristotle’s Physics: On the Nature of Time, 2015)
The key to taking in Aristotle’s treatise on time is to approach it with the understanding that Aristotle was not a philosopher concerned with time —in questions about time or in delimiting the being of time.
Keywords: Accidental Change; Accidental Form; Natural Object; Predicative Change; Privative Form; dept.phi

Excellent online friendships: an Aristotelian defense of social media - Elder, Alexis (Ethics and Information Technology, 2014)
I defend social media's potential to support Aristotelian virtue friendship against a variety of objections. I begin with Aristotle's claim that the foundation of the best friendships is a shared life. Friends share the distinctively human and valuable components of their lives, especially reasoning together by sharing conversation and thoughts, and communal engagement in valued activities. Although some have charged that shared living is not possible between friends who interact through digital social media, I argue that social media preserves the relevantly human and valuable portions of life, especially reasoning, play, and exchange of ideas. I then consider several criticisms of social media's potential to host friendships, and refute or weaken the force of these objections, using this conception of a distinctively human shared life. I conclude that we should use the shared life to evaluate features of social media and norms for users' conduct.
Keywords: Aristotle; Data privacy; Friendship; Information technology; Privacy; Shared activity; Social media; Social networking (online); Social sciences; Valuable component; dept.phi

On the possibility of quantum informational structural realism - Bynum, Terrell Ward (Minds and Machines, 2014)
In The Philosophy of Information, Luciano Floridi presents an ontological theory of Being qua Being, which he calls "Informational Structural Realism", a theory which applies, he says, to every possible world. He identifies primordial information ("dedomena") as the foundation of any structure in any possible world. The present essay examines Floridi's defense of that theory, as well as his refutation of "Digital Ontology" (which some people might confuse with his own). Then, using Floridi's ontology as a starting point, the present essay adds quantum features to dedomena, yielding an ontological theory for our own universe, Quantum Informational Structural Realism, which provides a metaphysical interpretation of key quantum phenomena, and diminishes the "weirdness" or "spookiness" of quantum mechanics. © 2013 The Author(s).
Keywords: Dedomena; Digital ontology; Primordial qubit; Quantum information; Structural realism; dept.phi

Association and asylum - Cavallero, Eric (Philosophical Studies, 2014)
Keywords: dept.phi

Zhuangzi on friendship and death - Elder, Alexis (Southern Journal of Philosophy, 2014)
Zhuangzi suggests that death is a transformation that we commonly and mistakenly think means the end of someone but really just marks a new phase of existence. This metaphysical thesis is presented at several points in the text as an explanation of distinctively Daoist responses to death and loss. Some (such as Wong 2006) take a Daoist response to death, as presented by Zhuangzi, to indicate dual perspectives on friendship and death. But I argue that the metaphysical view sketched above is consistent with a unified perspective, allowing the Daoist to enjoy deep friendships without risking some potential for grief typically associated with strong attachment. However, it leaves the Daoist best suited to friendships with those who endorse the same metaphysics. Furthermore, while the grief associated with the death of a friend is somewhat mitigated, the Daoist has reason to mourn even given this thesis. © 2014 The University of Memphis.
Keywords: dept.phi

Situating the early schelling in the later positive philosophy - Harry, Chelsea C (Comparative and Continental Philosophy, 2014)
This is a translation of the second chapter of F.W.J. Schelling's Abhandlungen zur Erlaüterung des Idealismus der Wissenschaftslehre (1796-1797). It is preceded by a brief introduction in which I situate the chapter within Schelling's oeuvre and suggest that it is not only an early articulation of Schellingian Naturphilosophie, but also prescient, anticipating Schelling's later positive philosophy. © W. S. Maney & Son Ltd 2014.
Keywords: Naturphilosophie; Negative philosophy; Positive philosophy; Schelling; dept.phi

Helping students to see for themselves that ethics matters - Jagger, Suzy; Volkman, Richard (The International Journal of Management Education, 2014)
Business ethics education is experiencing a renaissance as recurring corporate scandals and malpractice over the last decade have ensured that most universities now see the subject as an important and necessary component of any business degree course. As well as integrating professional ethics into their curriculum, Business Schools are also developing standalone ethics courses, showing that they take seriously their responsibility to help prepare the next generation of managers to improve business' track record of transparency, accountability and sustainable development. However what are the learning approaches that will help to bring about real improvements in business ethics learning at university? This paper argues that a holistic approach to ethics teaching is needed, in which students are encouraged to develop ethical knowledge and skills within their personal value systems. In this way ethics does not become something apart but integrated into one's terms of reference. The paper discusses a particular pedagogic approach designed to develop a student's 'critical consciousness' using a student-led learning method in which students actively engage with important concepts and discuss the issues amongst themselves within an environment where they can speak freely. Qualitative interviews with a selection of undergraduates on the compulsory first year professional ethics module provide insight into the impact of the method on attitudes and behaviours. © 2013 Elsevier Ltd.
Keywords: Business ethics; Moral sensitivity; Teaching business ethics; Transformational learning; Values and integrity; Virtue ethics; dept.phi

The making of modern Turkey: nation and state in eastern Anatolia, 1913–1950 - Marsoobian, Armen T (Journal of Genocide Research, 2013)
Keywords: dept.phi

Collective intelligence and ethical individualism - Volkman, Richard (ACM Sigcas Computers and Society, 2013)
Keywords: dept.phi

Creating the Journal Metaphilosophy - Bynum, Terrell Ward (Metaphilosophy, 2011)
This brief article describes the circumstances that led to the creation of the journal Metaphilosophy in autumn 1968. A year after I had left graduate school, an unfortunate accident left me flat on my back for several weeks with nothing to do while recuperating from eye surgery. Bored, I decided to do something constructive, so I created a scholarly journal devoted to articles about the nature of philosophy, or how the different schools or branches of philosophy relate to each other, or how philosophy relates to other disciplines. I made up the word "metaphilosophy" to describe such content, and I decided to call the journal by that name. With help from my wife, from my best friend, and from my undergraduate philosophy mentor, the journal Metaphilosophy was launched. © 2011 Metaphilosophy LLC and Blackwell Publishing Ltd.
Keywords: dept.phi; editorial board; metaphilosophy; scholarly journal

Health, luck and moral fallacies of the second best - Cavallero, Eric (The Journal of Ethics, 2011)
Individuals who become ill as a result of personal lifestyle choices often shift the monetary costs of their healthcare needs to the taxpaying public or to fellow members of a private insurance pool. Some argue that policies permitting such cost shifting are unfair. Arguments for this view may seem to draw support from luck egalitarian accounts of distributive justice. This essay argues that the luck egalitarian framework provides no such support. To allocate healthcare costs on the basis of personal responsibility would arbitrarily and publicly burden socially detectable risk-takers while undetectable risk-takers continue to get a free ride. That problem is unavoidable even on the assumption that distributive institutions outside the healthcare sector are fully just. In actual, farfrom-just societies, imposing personal liability for the costs of voluntary risk taking would be wrong for an additional reason. Doing so would tend to magnify existing distributive injustices. These conclusions draw attention to two common 'moral fallacies of the second best' that can arise when applying ideal normative theory to matters of institutional design and in real-world policy contexts. © 2011 Springer Science+Business Media B.V.
Keywords: Egalitarianism; Health; Healthcare; Luck; Luck egalitaianism; Personal responsibility; Responsibility; dept.phi; peer-reviewed

Coercion, inequality and the international property regime - Cavallero, Eric (Journal of Political Philosophy, 2010)
Keywords: dept.phi

Philosophy in the Information Age - Bynum, Terrell Ward (Metaphilosophy, 2010)
Abstract: In the past, major scientific and technological revolutions, like the Copernican Revolution and the Industrial Revolution, have had profound effects, not only upon society in general, but also upon Philosophy. Today's Information Revolution is no exception. Already it has had significant impacts upon our understanding of human nature, the nature of society, even the nature of the universe. Given these developments, this essay considers some of the philosophical contributions of two “philosophers of the Information Age”—Norbert Wiener and Luciano Floridi—with regard to the nature of the universe, human nature, the nature of society, and the nature of “artificial agents” such as robots, softbots, and cyborgs.
Keywords: Artificial agents; Cybernetics; Cyborgs; Digital physics; Entropy; Inforg; Information; Information Age; Information Revolution; Information age; Information revolution; Infosphere; Luciano Floridi; Norbert Wiener; Qubits; Robots; Second law of thermodynamics; artificial agents; cybernetics; cyborgs; dept.phi; digital physics; entropy; inforg; information; infosphere; qubits; robots; second law of thermodynamics

Commodification and privacy: a Lockean perspective. - Volkman, Richard (HEC forum : an interdisciplinary journal on hospitals' ethical and legal issues, 2010)
This paper defends the thesis that privacy as a right is derived from fundamental rights to life, liberty, and property and does not permit restricting the commodification of bodily material; however, privacy as life, liberty, property does require conventions that ensure a robust and just market in bodily material. The analysis proceeds by defending a general commitment to liberty and markets, but not in the manner one might expect from a 'doctrinaire' libertarian. Ethical concerns about commodification are legitimate in the context of new medical and information technologies, but these concerns are not sufficiently well defined to justify political conclusions, since not every ethical concern is in itself a political concern, and the best way to resolve certain ethical difficulties is to draw up political boundaries that facilitate the discovery and testing of various solutions to our ethical puzzles. To illustrate the point, I will indicate how privacy as life, liberty, property defines such a dynamic solution to the problems of commodification of human bodily material and slippery information in insurance markets.
Keywords: *Ownership; *Privacy; Civil Rights; Commerce; Commodification; Human Body; Humans; John Locke; Liberalism; Markets; Natural rights; Ownership; Politics; Privacy; art; article; civil rights; commercial phenomena; dept.phi; human; organization and management; politics; privacy

Why information ethics must begin with virtue ethics - Volkman, Richard (Metaphilosophy, 2010)
The information ethics (IE) of Floridi and Sanders is evaluated here in the light of an alternative in virtue ethics that is antifoundationalist, particularist, and relativist in contrast to Floridi's foundationalist, impartialist, and universalist commitments. Drawing from disparate traditional sources like Aristotle, Nietzsche, and Emerson, as well as contemporary advocates of virtue ethics like Nussbaum, Foot, and Williams, the essay shows that the central contentions of IE, including especially the principle of ontological equality, must either express commitments grounded in the particular perspectives we already inhabit, or be without rational or ethical force for us. © 2010 Metaphilosophy LLC and Blackwell Publishing Ltd.
Keywords: Ethical individualism; Foundationalism; Information ethics; Particularism; Virtue ethics; dept.phi

The genocidal legacy of Radovan Karadžić - Pettigrew, David (Etnické komunity: hrdinové, šibalové a antagonisté Balkánu, 2017)
Keywords: dept.phi

Opportunity and responsibility for health - Cavallero, Eric (The Journal of Ethics, 2019)
Wealth and income are highly predictive of health and longevity. Egalitarians who maintain that this “socioeconomic-status gradient” in health is unjust are challenged by the fact that a significant component of it is owed to the higher prevalence of certain kinds of voluntary risk-taking among members of lower socioeconomic groups. Some egalitarians have argued that these apparently free personal choices are not genuinely free, and that those who make them should not be held morally responsible for the resulting harms to their health. I argue to the contrary that such choices usually are fully free, and that those who make them are responsible for their consequences. This does not imply, however, that society cannot also be responsible for those consequences. It is responsible for them if they are statistically foreseeable and avoidable outcomes of unjust public institutions and policies. I show that many of the harms to health that contribute to the voluntary behavioral component of the SES health gradient satisfy that description. Society can therefore be morally responsible for those harms, even though the individuals who suffer them are also fully responsible for them.
Keywords: Equality of opportunity; Health; Personal responsibility; SES gradient in health; Social responsibility; dept.phi; peer-reviewed

How do we make sense of the thesis “bai (white) ma (horse) fei (is not) ma (horse)”? - Yang, Xiaomei (Dao, 2019)
In this article, I introduce a new interpretation of the puzzling thesis “bai 白 (white) ma 馬 (horse) fei 非 (is not) ma 馬 (horse)” argued by Gongsun Long 公孫龍 in his essay “On White Horse (Bai Ma Lun 白馬論).” I argue that previous interpretations, which can be grouped under the name of “attribute-object interpretations,” are not satisfactory, and that the thesis on the new interpretation is not about attributes or objects, but about names. My argument focuses on the disagreement over inseparability of white (shou bai zhi zheng 守白之爭) between Gongsun Long and his interlocutor in the text of “On White Horse.” On my interpretation or the name interpretation, the disagreement is about whether constituents of a syntactically complex or multi-term name are separable or have their contextually independent meanings. Gongsun Long’s thesis makes perfect sense on my interpretation, and is supported by the text and other preserved texts collected in GongsunLong Zi 公孫龍子. The name interpretation can also make sense of some puzzling expressions of sophists in the classic period.
Keywords: Complex name; Descriptive phrase; Inseparability of white; Simple name; White Horse; dept.phi; peer-reviewed

Exchanging IRL for VR: experience machines and opportunity costs - Volkman, Richard (ACM SIGCAS Computers and Society, 2018)
Virtual Reality (VR) experiences have arrived for a wide audience, and some worry that VR experience entices us to abandon experience In Real Life (IRL). While such worries cannot be dismissed out of hand, they are liable to be imprecise and distorted without careful analysis of the opportunity costs of VR experience. Generally, we are not liable to abandon real experience for its virtual analogue. Even a perfect VR experience is generally not a perfect substitute for a like experience IRL. Instead, the success of VR will depend on its ability to produce experiences valued for what they actually are.
Keywords: dept.phi; experience machine; value theory; virtual reality

Criticism and compassion: the ethics and politics of Claudia Card - Dillon, Robin S.; Marsoobian, Armen T. (Wiley, 2018)
Criticism and Compassion: The Ethics and Politics of Claudia Card offers a unique perspective on the range of issues explored by Card during her distinguished career in philosophy. Investigates her work as an early leader in the development of feminist philosophy, challenging many preconceptions about the society’s norms regarding gender, marriage, and motherhood Crossing many disciplinary boundaries, her concept of social death has come to play a significant role in multidisciplinary field of genocide studies This volume combines many of Claudia Card’s important essays with recently commissioned essays by leading philosophers whose work has been influenced by Card The full scope of Card’s philosophy is presented here - both in her own words and those of her critics and interpreters
Keywords: dept.phi

Collective memory, memorialization and bearing witness in the aftermath of the Armenian Genocide - Marsoobian, Armen T. (Multidisciplinary Perspectives on Genocide and Memory, 2018)
This chapter describes and analyzes an ongoing project of memorialization of the Armenian Genocide in Turkey. It explores the importance of memorialization for collective historical memory, especially in situations where historical memory has been subverted by genocide denial. Among many aspects of memorialization, its role in bearing witness is explored and highlighted. Three components of the memory project are described: (1) the photography exhibitions, (2) the publications, and (3) the creation of memory sites. The project centers on the story of the Dildilian family in Ottoman Turkey before, during, and after the genocide, covering the years 1872–1923. A microhistory of the life of the Armenian minority is chronicled by means of the personal memories and stories of members of the family. The history is richly illustrated with photographs and drawings that serve as the basis of the photography exhibitions and books. Exhibitions and associated talks and panels have taken place in Istanbul, Merzifon, Diyarbakir, and Ankara. The chapter describes and analyzes the reaction of the Turkish public to the project.
Keywords: Armenian Genocide; Bearing witness; Collective memory; Genocide denial; Memorialization; Turkey; dept.phi

How do we memorialize genocide? The case of the German memorial to the murdered Jews of Europe - Marsoobian, Armen T (Multidisciplinary Perspectives on Genocide and Memory, 2018)
This book explores the memory and representation of genocide as they affect individuals, communities and families, and artistic representations. It brings together a variety of disciplines from public health to philosophy, anthropology to architecture, offering readers interdisciplinary and international insights into one of the most important challenges in the 21st century. The book begins by describing the definitions and concepts of genocide from historical and philosophical perspectives. Next, it reviews memories of genocide in bodies and in societies as well as genocide in memory through lives, mental health and transgenerational effects. The book also examines the ways genocide has affected artistic works. From poetry to film, photography to theatre, it explores a range of artistic approaches to help demonstrate the heterogeneity of representations. This book provides a comprehensive and wide-ranging assessment of the many ways genocide has been remembered and represented. It presents an ideal foundation for understanding genocide and possibly preventing it from occurring again
Keywords: Aesthetics; Counter-monument; Health Psychology; Health psychology; History of World War II and the Holocaust; Holocaust; James E. Young; Jochen Gerz; John Dewey; Marian Marzynski; Memorial to the Murdered Jews of Europe; Memorial to the murdered jews of europe; Modernism; Noël Carroll; Peter Eisenman; Public Health; Public health; Public memorials; Sociology; Sociology, general; World War, 1939-1945; dept.phi

The suppression of cultural memory and identity in Bosnia and Herzegovina - Pettigrew, David (Multidisciplinary Perspectives on Genocide and Memory, 2018)
This chapter identifies an orchestrated effort in “Republika Srpska”—an entity within Bosnia and Herzegovina that was recognized by the 1995 Dayton Peace Agreement − that is designed to prevent survivors of the genocide from erecting memorials to the victims in such locations as Višegrad, Prijedor, and Foča. While memorials for victims have been prohibited, and survivors have been prevented from using the term “genocide,” memorials to the perpetrators have been installed in the center of Višegrad, and near the Trnopolje concentration camp in Prijedor Municipality. In the hills above Sarajevo, in a location from which the city’s residents were attacked during the siege, a plaque honoring indicted war criminal Ratko Mladić has been installed. Accordingly, this chapter considers the extent to which the discriminatory practices regarding memorials in Republika Srpska constitute a violation of human rights. Further, the chapter argues that, following Raphael Lemkin’s definition of genocide, the prohibitive policies in Republika Srpska with respect to memorials and commemorative practices constitute nothing less than a continuation of the genocide, a second phase of the genocide designed to ensure the permanent erasure of a world that was destroyed. These human rights violations and the continuation of the genocide are a troubling testament to the failure of the international community in Bosnia, and to the problematic legacy of the Dayton Peace Agreement.
Keywords: Apartheid; Cultural memory; Dayton Peace Agreement; Dayton peace agreement; Health Psychology; Health psychology; History of World War II and the Holocaust; Human rights; Prohibited memorials; Public Health; Public health; Raphael Lemkin; Sociology; Sociology, general; World War, 1939-1945; dept.phi

Value individualism and the popular-choice theory of secession - Cavallero, Eric (Social Theory and Practice, 2017)
Keywords: dept.phi